Resultant of an equivariant polynomial system with respect to the symmetric group. (September 2016) - Busé, Laurent; Karasoulou, Anna
Abstract: Given a system of n ⩾ 2 homogeneous polynomials in n variables which is equivariant with respect to the symmetric group of n symbols, it is proved that its resultant can be decomposed into a product of several resultants that are given in terms of some divided differences. As an application, we obtain a decomposition formula for the discriminant of a multivariate homogeneous symmetric polynomial.